Phytoremediation of Phenol at pilot scale by tobacco hairy roots - Sosa Alderete, Lucas Gastón (2012)
Phenol is a toxic compound commonly found in the wastewater released from several industries. In the present work, we optimized the use of tobacco hairy roots (HRs), wild type (WT) and double transgenic (DT) for two peroxidases, as an alternative strategy for the treatment of this pollutant. The optimal conditions for the removal process were evaluated using different phenol (100-800 mg L-1) and H2O2 (2,5-10 mM) concentrations. Tobacco HRs were able to remove solutions with increasing phenol concentrations. Regarding the effect of exposition time, prolonged time of treatment improved phenol remediation when high pollutant concentrations were used. A decrease in basic peroxidase (Px) isoenzymes was detected after phenol treatment. Kinetic studies were performed using different Px extracts, such as soluble Px (SPx) and ionically bound Px (IBPx) from WT and DT HRs. SPx and IBPx extracts from DT HRs, showed high affinity towards phenol as substrate and higher catalytic efficiency than extracts derived from WT HRs. Moreover, IBPx extract from DT HRs, showed the highest catalytic efficiency, demonstrating that these HRs could provide an adequate matrix for the successful phenol removal.